Characterization of ginsenoside extracts by delayed luminescence, high-performance liquid chromatography, and bioactivity tests. Issue 5 (15th February 2019) - Sun, Mengmeng; He, Min; Korthout, Henrie; Halima, Mahmoud; Kim, Hye Kyong; Yan, Yu; van Wijk, Eduard; van Wijk, Roeland; Guo, Chunsheng; Wang, Mei
Abstract : Delayed luminescence measurements show the same results in terms of differentiating ginsenoside extracts compared with chemical analysis. Abstract : Ginsenoside extracts are often used as raw materials for various pharmaceutical, cosmetic and food supplement products. Development of a direct, rapid, cheap, and comprehensive measurement tool for the quality assessment of ginsenoside extracts, and indeed all herbal extracts, is urgently needed. In addition, a bioactivity-based assessment should be linked with quality control. In this report, we try to develop a novel quality control tool using ginsenoside extracts as an example. High-performance liquid chromatography (HPLC) was used to detect nine principal ginsenosides in 11 batches of ginsenoside extracts. Delayed luminescence (DL) was used to analyze the same ginsenoside extract samples. DL measurements showed the same results in terms of differentiating 11 ginsenoside extract samples compared with chemical analysis, and DL properties could be closely linked to index ginsenosides in the quality control of ginsenoside extracts. Next, a zebrafish tail-fin amputation model was used to study differences in anti-inflammatory effect between the ginsenoside extract batches. The results indicate that both chemical analysis and DL measurements could partially reflect biological activity. Thus, DL may serve as a rapid, direct, sensitive, and systemic tool for studying the overall properties of ginsenoside extracts. Our proposal for linking bioactivities as a tool for evaluation of the quality of ginsenoside extracts opens a new direction for quality control.